'Prevent undernutrition and prescribe oral nutritional supplements correctly': an educational intervention for district nurses. (2019) - Samuelsson, L.; Södergren, M.; Berggren, E.; Törnkvist, L.
Abstract: Aim: The aim of this study was to evaluate district nurses' (DN) perceived nutritional care and actual level of knowledge about nutritional care before and after a continuing educational intervention. Background: Nutritional treatment is an important part of nursing care, and health professionals responsible for nutritional care for older adults must therefore have sufficient understanding of nutritional problems to provide appropriate support. Previous research has shown that nutritional problems frequently go unrecognized and that health care personnel often lacks knowledge about nutritional care and relevant methods of assessing nutritional status. However, little is known about DNs' knowledge about nutritional care. Methods: An evaluative study with a study-specific questionnaire administered before and after a 2.5-day continuing educational course for DNs in primary health care in Stockholm County, Sweden. The course was given over a period of two to three months. The questionnaire measured DNs' perceived nutritional care and actual level of knowledge about nutritional care. Findings: A total of 456 DNs completed the questionnaire both before and after the intervention. Participants' mean age was 50 years. They had worked a mean of 26 years in health care and 10 years as DNs. Before the intervention, many DNs reported that they did not work with nutritional care in an optimal way. After the intervention, significant improvements were found in perceived nutritional care and actual level of knowledge about the topic. However, not all DNs achieved the learning objectives of the course, so work remains to be done to ensure that DNs have sufficient knowledge of nutritional care to provide appropriate support and correctly prescribe oral nutritional supplements. Conclusions: The study provides new information on DNs' perceived nutritional care and actual level of knowledge. The result of the intervention helps lay the foundation for good nutritional care for older patients in primary care.